3D Self‐Supported Fe‐Doped Ni2P Nanosheet Arrays as Bifunctional Catalysts for Overall Water Splitting. (4th August 2017) - Li, Yingjie; Zhang, Haichuan; Jiang, Ming; Zhang, Qian; He, Peilei; Sun, Xiaoming
Abstract : The development of highly efficient bifunctional electrocatalysts for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is crucial for improving the efficiency of overall water splitting, but still remains challenging issue. Herein, 3D self‐supported Fe‐doped Ni2 P nanosheet arrays are synthesized on Ni foam by hydrothermal method followed by in situ phosphorization, which serve as bifunctional electrocatalysts for overall water splitting. The as‐synthesized (Ni0.33 Fe0.67 )2 P with moderate Fe doping shows an outstanding OER performance, which only requires an overpotential of ≈230 mV to reach 50 mA cm −2 and is more efficient than the other Fe incorporated Ni2 P electrodes. In addition, the (Ni0.33 Fe0.67 )2 P exhibits excellent activity toward HER with a small overpotential of ≈214 mV to reach 50 mA cm −2 . Furthermore, an alkaline electrolyzer is measured using (Ni0.33 Fe0.67 )2 P electrodes as cathode and anode, respectively, which requires cell voltage of 1.49 V to reach 10 mA cm −2 as well as shows excellent stability with good nanoarray construction. Such good performance is attributed to the high intrinsic activity and superaerophobic surface property. Abstract : 3D self‐supported Fe‐doped Ni2 P nanosheet arrays are fabricated by hydrothermal method and in situ phosphorization. The performance of the nanosheet arrays toward overall water splitting depends on the Fe doping ratio. An alkaline electrolyzer using two identical (Ni0.33 Fe0.67 )2 P nanosheet arrays electrodes can operate at 10 mA cm ‐2 under 1.49 V.